Special public investment projects and the public investment execution model: review of the tools that can be used to improve government contracting - Medina Flores, Juan Carlos (2021)
After the XVIII Pan American Games and Sixth Parapan American Games were held between July and September 2019, the largest sporting event organized and executed by Peru, which involved the deployment of novel contracting and management mechanisms, the Government has sought replicate this experience in a new investment management model. In this context, the Special Public Investment Projects were created, with the aim of applying this new investment management model for the execution of public investment projects, a package of projects or a portfolio of projects.The regulation of these Special Public Investment Projects has been progressively developed in the last year, adopting even the mechanism of Government-to-Government contracts. This regulatory development has led to the creation of the first Public Investment Project, “Escuelas Bicentenario”. With the constant announcements of modification of the Government Procurement Law, the discussion of the opportunity and relevance of implementing the tools enabled for Special Public Investment Projects in the general regulation of public contracts has been raised, in order to improve the execution of public works. In this scenario, it is important to study the tools considered in the investment execution model envisaged in Emergency Decree 021-2020, as a starting point to evaluate the proposals for improvement to the Government Procurement Law. In this article the main tools of the Investment Execution Model are reviewed, as well as the benefits these tools provide for the execution of important infrastructure projects in Peru.